2019
DOI: 10.3389/fonc.2019.00392
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA-100338 Is Associated With mTOR Signaling Pathway and Poor Prognosis in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the leading cause of cancer-related deaths worldwide. Despite advances in the diagnosis and treatment of HCC, incidence, and mortality continue to rise. For accurate diagnosis and treatment of HCC, there is an urgent need to precisely understand the molecular mechanisms underlying HCC tumorigenesis and progression. Accumulating evidence showed that circRNAs, which are normally produced by scrambling of exons at the splicing process, are recognized as a novel class of endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 40 publications
0
71
0
Order By: Relevance
“…circRNAs were identified to be important regulators in human cancers. In HCC, we, together with other research teams [5][6][7], have identified that a series of cir-cRNAs were dysregulated in cancer samples and associated with tumor progression, which may serve as promising biomarkers for cancer. CircRNAs are involved in regulating multiple cancer-related biological processes and pathways, including cell growth [8], metastasis [9], and apoptosis [10].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…circRNAs were identified to be important regulators in human cancers. In HCC, we, together with other research teams [5][6][7], have identified that a series of cir-cRNAs were dysregulated in cancer samples and associated with tumor progression, which may serve as promising biomarkers for cancer. CircRNAs are involved in regulating multiple cancer-related biological processes and pathways, including cell growth [8], metastasis [9], and apoptosis [10].…”
Section: Introductionmentioning
confidence: 90%
“…The HCC cell lines were cultured following procedures stated in our previous reports [5,12]. Briefly, the noninvasive human liver cell line of L02 (normal), human HCC cell lines of Hep3B with low invasiveness, and highly invasive HLE, Huh7, BEL7402, SMCC7721, MHCC97L, MHCC97H, HCCLM3 and HCCLM6 were prepared in this study, which were widely used in previous studies [17,18].…”
Section: Hcc Cell Line and Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…recent studies have indicated that circrnas may serve important roles in driving cancer initiation and progression, and have the potential to serve as biomarkers for predicting cancer progression (7,8). accumulating evidence has demonstrated that circrnas regulate Hcc progression and serve as potential biomarkers for predicting cancer prognosis (9)(10)(11)(12)(13)(14)(15). However, a considerable number of circrnas remain to be elucidated in Hcc.…”
Section: Introductionmentioning
confidence: 99%